Pemanfaatan Media Sosial untuk Mempromosikan Produk Minyak Kelapa BUMDes Iwekahalesan di Kabupaten Minahasa Tenggara - Yola Ningsi Samual; Nancy Henrietta Jessamine Mandey; Maya Munaiseche; Sulastri Eksan; Grace Pontoh (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
Coconut is one of the mainstay products of North Sulawesi, the result is coconut oil. BUMDes Iwekahalesan has produced and managed the sale of coconut oil products, but it is still very simple so that it has not given maximum profit. Therefore, this study aims to design promotional media so that these products can be sold in a wider market. Interview method is used to obtain information related to promotional activities that will be carried out. Promotional media that can be made such as logos, receipts, labels, social media (facebook and instagram. It is hoped that this product can be sold more after promotion using social media